Prevention of Protein Degradation Using Ensiling Coffee Husk - Suci Wulandari; Rizki Amalia Nurfitriani; Satria Budi Kusuma (Jurnal Ilmu-Ilmu Peternakan, 2023)
The purpose of this research is to provide protein protective compounds during the ensiling process using local materials, namely coffee husk waste. The type of coffee used was robusta. Dry coffee husk (moisture <15%) was ground using a Wiley mill (2 mm sieve). The extraction of tannins from coffee husk waste was performed by the Soxhlation method using ethanol organic solvent (70%). The research involved four treatments and five replications, namely P0= elephant grass silage without tannins; P1= elephant grass silage with the mixture of 3g coffee husk tannins per 1kg fresh silage; P2= elephant grass silage with the mixture of 6g coffee husk tannins per 1kg fresh silage; and P3= elephant grass silage with the mixture of 9g coffee husk tannins per 1kg fresh silage. A completely randomized design (CRD) was employed. The significantly different results were then tested using Duncan's Multiple Test (DMRT). In summary, the addition of coffee husk tannins with a dose of 9g per 1kg of fresh silage presented the best quality elephant grass silage.